2010
DOI: 10.1099/mic.0.038018-0
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica subspecies enterica serovar Enteritidis Salmonella pathogenicity island 2 type III secretion system: role in intestinal colonization of chickens and systemic spread

Abstract: Salmonella enterica subspecies enterica serovar Enteritidis (S. Enteritidis) has been identified as a significant cause of salmonellosis in humans. Salmonella pathogenicity islands 1 and 2 (SPI-1 and SPI-2) each encode a specialized type III secretion system (T3SS) that enables Salmonella to manipulate host cells at various stages of the invasion/infection process. For the purposes of our studies we used a chicken isolate of S. Enteritidis (Sal18). In one study, we orally co-challenged 35-day-old specific path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Interestingly, Wisner et al [35], showed that the Salmonella was cleared after 3 and 4 days of post challenge which suggests that testing the feces could have helped in finding specific inoculated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wisner et al [35], showed that the Salmonella was cleared after 3 and 4 days of post challenge which suggests that testing the feces could have helped in finding specific inoculated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Desin et al (2009) states that S. Enteritidis mutants deficient in the entire SPI-1 (ΔSPI-1) were able to colonize chicken caeca at the same level as the non-mutant wildtype (wt). Mutant strains ΔSPI-1 and ΔSPI-2 were out-competed by wt strains during colonization but reached the same level of systemic spread at a slower rate than parent strains (Wisner et al, 2010). Together this suggests that changes within S. Sofia SPI-1 and 2 compared to S. Typhimurium may not play a major role in this organism's successful colonisation of chickens.…”
Section: Spimentioning
confidence: 96%
“…To examine this, chickens were challenged orally with 10 6 -10 9 Salmonella bacteria. In co-challenge trials using 35-day-old chickens we showed that although a S. Enteriditis wild-type strain was only slightly more competitive in colonizing the ceca than mutants defective in SPI-1 and SPI-2, the systemic spread of both of these mutant strains to the liver and spleen was significantly less successful than that of the wild-type strain (Desin, et al, 2009, Wisner, et al, 2010. Colonization of the gut was nearly 100% for both wild-type and mutants, whereas Salmonella was detected in the liver and spleen in approximately 30% of the birds in these trials.…”
Section: Role Of the Salmonella Pathogenicity Island-1 And -2 Type IImentioning
confidence: 96%